OPTIMIZATION OF WIRELESS PRICING SCHEME - Puspita, Fitri Maya; Taib, Bahok M.; Abdullah, Ismail (Prosiding International conference on Information Technology and Business (ICITB), 2015)
The wireless service providers obtain surplus fromconsumers who applied the service. That pricing strategyis developed by considering the linearity factors, elasticityprice, price factors, acceptance factor and unit serviceprice. Previous researches are focussed on the introductionof the models in general. This new approach of the modelis by considering the model as the nonlinear programmingproblem that can be solved optimally using LINGO 13.0.The optimal solution could give information on decisionvariables and objective function to maximize the revenuefor the providers. The several objectives to be achieved byservice providers are by setting the increment ordecrement of price change due to QoS change and amountof QoS value.KEY WORDS: Optimization, price change, QoS change, amount of QoSvalue